Pendampingan Integrasi Computer Assisted Instruction dan Internet of Things Berbasis HOTS untuk Peningkatan Kompetensi Guru SMA - Rustam Efendy Rasyid; Jumiati; Nurmayanti; Nurhaedah; Herawati (LP2M INSURI Ponorogo, 2025)
This community service research aims to improve the competence of SMA Negeri 1 Sidrap teachers in designing and implementing learning based on Higher Order Thinking Skills (HOTS) through the integration of Computer-Assisted Instruction (CAI) and the Internet of Things (IoT). This activity was motivated by teachers' low understanding of the HOTS learning strategy, the limitations of the use of CAI, and the lack of application of IoT in supporting contextual learning according to the demands of the Independent Curriculum. The method used is a participatory-collaborative approach with several stages, namely socialization, intensive training, application of technology in the classroom, mentoring and evaluation, and preparation of good practice guidelines as a form of program sustainability. Data was collected through observations, interviews, pre-training and post-training questionnaires, and activity documentation. The results of the activity showed that there was an increase in teachers' competence in designing HOTS teaching devices, utilizing interactive CAI modules, and integrating simple IoT in project-based learning. In addition, this activity strengthens the capacity of educational institutions through the development of adaptive technology-based learning models, increasing student involvement, and placing SMA Negeri 1 Sidrap as a model school in the implementation of CAI and IoT-based HOTS learning.